INCREASE PERFORMANCE OF CIVIC EDUCATION THROUGH SCRAMBLE FOR STUDENT CLASS V SDN 1 KEDIRI - Sulistyaningsih, Erika (PROGRES PENDIDIKAN, 2024)
This research aims to know the enhancement performance Study student on eye lesson PPKn use model Scramble learning for class V students at SD Negeri Tangga 1. Study held in Subdistrict Gesi, Regency Sragen, Province Java Middle. Study This is Study Classroom Action (PTK) uses the scramble learning model with do stages planning, action, observation/observation, reflection. Subject study this is student class V of SD Negeri Tanggan 1 for the 2022/2023 academic year. Technique collecting data by observation, tests, and documentation. Analysis data use formula percentage. The research results show an increase in learning achievement. There is enhancement on mark average student from 62.78 on implementation pre cycle become 71.78 on cycle I. And There is enhancement return become 81.64 on cycle II. Ascension the Also happen on amount student Which value sufficient Criteria Completeness Minimum (KKM) ie ≥75. In pre cycle only There is One student (7.14%) Which fulfil KKM. Then to eight students (57.14%) Increase in cycle I. And in cycle II to 12 students who met the KKM or 85.71% of all students. So with these results, this research can reach target with exists more from 75% student Which obtain mark in accordance with the KKM ie ≥75.